Multifunctional waterborne polyurethane coating liquid as well as preparation method and application thereof
By synthesizing an aqueous polyurethane coating on the fabric, using the reaction of bihydroxyl mono-terminated polydimethylsiloxane and diisocyanate to form an urethane group, and adding a hydrophilic chain extender, the problem of difficult coatings on fabrics in the prior art is solved, and efficient waterproof and stain-proof performance and environmentally friendly production process are achieved.
Patent Information
- Application Number
- CN202411904411.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, coatings with molecular brush structures are difficult to prepare on fabrics, and organic solvents are used in large quantities during the preparation process, and low-surface energy substances are difficult to disperse in water.
By reacting bihydroxyl mono-terminated polydimethylsiloxane, terminal hydroxy oligomer with diisocyanate to form an urethane group and adding bihydroxyl hydrophilic chain extender, the aqueous polyurethane emulsion that can be applied to fabrics is synthesized. This method can not only form a molecular brush-like structure, improve the waterproof and stain-proof performance of the fabric, but also disperse well in water and avoid the use of organic solvents.
It has achieved the preparation of efficient waterproof and anti-fouling coatings on fabrics, with excellent water repellent, graffiti-proof, self-cleaning and anti-static properties, while avoiding the use of organic solvents, meeting the requirements of environmental protection and high efficiency.
Smart Images

Figure CN119751808A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a multifunctional waterborne polyurethane coating liquid and a preparation method and application thereof. Background Art
[0002] Waterproof fabric coatings are widely used in outdoor clothing, home textiles, footwear, tents, bags and other fabrics. Their main function is to improve the weather resistance and comfort of fabrics by blocking water penetration. There are two key factors in the construction of waterproof fabric surfaces: (1) hydrophobic modification of the material surface with low surface energy substances; (2) changing the surface roughness of the substrate. The super-hydrophobic effect can be achieved by controlling the surface chemical properties and morphological structure. In terms of construction methods, chemical vapor deposition is a commonly used technology that can evenly deposit low surface energy materials on the fabric surface; solution coating method dissolves hydrophobic materials in solvents for impregnation or coating, and then forms a hydrophobic layer by drying or curing. In addition, surface etching technology is also commonly used to increase the roughness of the fabric surface, introduce micro-nano structures through chemical or mechanical etching, and then combine with hydrophobic coating treatment to further improve hydrophobicity. Commonly used materials include organic silicon compounds (methyl silane, chlorosilane and ethyl silane, etc.) and fluorine-containing compounds (perfluorooctane sulfonyl compounds PFOS and perfluorooctanoic acid PFOA, etc.), which can effectively reduce surface energy and provide excellent hydrophobic properties. However, although long-chain perfluorinated compound waterproof coatings have low surface energy (~10-20 mN·m -1 ), in addition to producing a good waterproof effect, it can also make textiles oil-proof. However, perfluorinated compounds are stable in nature, difficult to degrade, bioaccumulative and toxic to a certain extent. They have now become a new global environmental pollutant. At present, countries have gradually controlled such compounds. Therefore, environmentally friendly, green and environmentally friendly fluorine-free waterproof fabric coatings have attracted widespread attention in recent years. However, there are significant problems with fluorine-free waterproof fabric coatings, namely, they are not oil-proof, have poor hygroscopicity and are prone to static electricity. Once stained with oil stains, they are difficult to clean and are prone to static electricity in a dry environment. Therefore, it is key to give such waterproof fabrics oil-proof properties, self-cleaning properties, hygroscopic properties and antistatic properties.
[0003] With the development of research on liquid-repellent surfaces, a new research field has flourished: the development of fully repellent molecular brush-like liquid surfaces (LLSs) by covalently grafting highly flexible polymer chains on solid surfaces. The flexibility of the grafted polymer chains makes the coating behave like a liquid, and the surface exhibits extremely low contact angle hysteresis (CAH), making it easy for various organic and aqueous liquids to slide. Among them, the polydimethylsiloxane (PDMS) molecular brush structure is the most typical. First of all, the molecular chain segments in PDMS are flexible and can swing freely, which is mainly caused by its special chemical structure. In the PDMS unit structure, the Si-O and Si-C bond lengths are respectively and Significantly longer than the CC bond length And the bond angle of Si-O-Si Bond angle greater than CCC These differences increase the distance between the methyl groups on a single silicon atom, and also increase the distance between the methyl groups on adjacent silicon atoms. Therefore, PDMS has a lower surface energy and can give the fabric excellent wetting properties. Secondly, the high reactivity of the hydroxyl groups in hydroxyl-terminated polydimethylsiloxane can fix its hydroxyl end at the coating interface, and its long chain extends into the air phase, effectively forming a molecular brush structure.
[0004] However, most of the current polysiloxane molecular brush coatings are limited to smooth substrate surfaces, such as glass slides and silicon wafers, and the methods are limited to surface grafting through active groups on the substrate surface; and the fabric coatings currently studied use more or less a large amount of organic solvents to disperse low surface energy substances during the preparation process, and the use of organic solvents not only increases production costs, but also harms the human body and the environment. The most ideal solvent is water, which is green, environmentally friendly, pollution-free, and low in cost, but low surface energy substances are difficult to disperse in water. Therefore, it is urgent to provide a waterproof and antifouling coating that can be applied to fabrics and has environmentally friendly raw materials. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the problem in the prior art that the coating with a molecular brush structure is difficult to prepare on a fabric and a large amount of organic solvent is used in the preparation process.
[0006] In order to solve the above technical problems, the present invention provides a multifunctional water-based polyurethane coating liquid and its preparation method and application. The present invention forms an urethane group by reacting dihydroxy mono-terminated polydimethylsiloxane, a terminal hydroxyl oligomer and a diisocyanate, and introduces a hydrophilic group by adding a dihydroxy hydrophilic chain extender to synthesize a water-based polyurethane emulsion that can be applied to fabrics. First, the PDMS molecular chain segment has the characteristics of flexibility and can swing freely, so the polydimethylsiloxane has liquid-like properties and excellent liquid repellency; secondly, by utilizing the single-terminated characteristics of the dihydroxy mono-terminated polydimethylsiloxane, its hydroxyl end can be fixed at the coating interface, and its long chain extends into the air phase, effectively forming a molecular brush-like structure. In addition, the synthesized polyurethane molecular structure contains hydrophilic components, so a polyurethane emulsion that disperses well in water can be obtained and the coating can be given a good antistatic function.
[0007] The first object of the present invention is to provide a method for preparing an aqueous polyurethane coating solution, comprising the following steps:
[0008] S1, heating the dihydroxy mono-terminated polydimethylsiloxane, the terminal hydroxyl oligomer and the diisocyanate in the presence of an organic solvent and a catalyst to obtain a polyurethane prepolymer;
[0009] S2, heating the polyurethane prepolymer and the dihydroxy hydrophilic chain extender to react to obtain polyurethane;
[0010] S3, mixing the polyurethane with a neutralizing agent, and dispersing them in water at a high speed to obtain the aqueous polyurethane coating liquid.
[0011] Furthermore, in step S3, the aqueous polyurethane coating liquid further comprises hydrophobic nano-silicon dioxide, wherein the mass ratio of the hydrophobic nano-silicon dioxide to the aqueous polyurethane coating liquid is
[0012] (2-10): 100. Adding hydrophobic nano-silica can further improve the waterproof and antifouling properties of waterborne polyurethane coatings.
[0013] Furthermore, in step S1, the mass ratio of the dihydroxy mono-terminated polydimethylsiloxane to the terminal hydroxyl oligomer is (2-8):1.
[0014] Furthermore, the dihydroxy hydrophilic chain extender in step S2 is selected from one or more of 2,2-dihydroxymethyl propionic acid, dodecyl dihydroxyethyl methyl ammonium chloride, and bis(2-hydroxyethyl) dimethyl ammonium chloride.
[0015] Furthermore, the terminal hydroxyl oligomer in step S1 is selected from one or more of terminal hydroxyl polyethylene glycol, polypropylene glycol, polybutylene glycol, and polybutadiene, wherein the molecular weight of the terminal hydroxyl oligomer is 1000-3000. When the molecular weight of the terminal hydroxyl oligomer is too large, the molecular chain density is small and the hydrophobic effect is not good. When the molecular weight of the terminal hydroxyl oligomer is too small, the film-forming property of the coating decreases and the fastness becomes low.
[0016] Furthermore, the diisocyanate in step S1 is selected from one or more of isophorone diisocyanate and hexamethylene diisocyanate;
[0017] The organic solvent is selected from one or more of acetone, ethyl acetate, butanone, tetrahydrofuran, N,N-dimethylformamide, and dichloromethane;
[0018] The catalyst in step S1 is selected from one or more of dibutyltin dilaurate, dimethylcyclohexylamine, and N,N-dimethylbenzylamine;
[0019] In step S3, the neutralizing agent is selected from one or more of triethylamine, dimethylethanolamine, diethylethanolamine, triethanolamine, N,N-dimethylethanolamine, and diethanolamine. The neutralizing agent is used to adjust the pH of the coating liquid to prevent affecting the stability, particle size and distribution, and film-forming properties of the emulsion.
[0020] Furthermore, during the heating reaction in step S2, a viscosity adjuster may be added to adjust the viscosity of the polymer, and the viscosity adjuster includes one or more of acetone, paraffin, microcrystalline wax, polyethylene wax, oxidized polyethylene wax, polypropylene wax, sasol wax, hyperbranched polymer, ethylene bisstearamide, ethylene-vinyl acetate copolymer, urea, hydroxylamine hydrochloride, hydroxylamine sulfate, and cyclohexanol.
[0021] Furthermore, the temperature of the heating reaction in step S1 is 70-90°C, and the time of the heating reaction is 15min-3h;
[0022] The temperature of the heating reaction in step S2 is 70-90° C., and the time of the heating reaction is 15 min-3 h.
[0023] Furthermore, steps S1-S3 are performed under an inert gas atmosphere.
[0024] The second object of the present invention is to provide an aqueous polyurethane coating liquid prepared by the above preparation method.
[0025] The third object of the present invention is to provide a waterproof, anti-graffiti and anti-static coating, wherein the waterproof, anti-graffiti and anti-static coating is prepared from the above-mentioned aqueous polyurethane coating liquid.
[0026] The fourth object of the present invention is to provide a waterproof, anti-graffiti and anti-static product, which contains the waterproof, anti-graffiti and anti-static coating mentioned above.
[0027] Furthermore, the waterproof, graffiti-proof and antistatic product includes a waterproof, graffiti-proof and antistatic fabric, which is obtained by applying the aqueous polyurethane coating liquid to the fabric, drying and curing the fabric, wherein the drying and curing temperature is 100-150° C., and the drying and curing time is 15 min-1 h.
[0028] Beneficial effects of the present invention:
[0029] (1) In view of the problems in the prior art that molecular brush structures are difficult to prepare on fabrics, that a large amount of organic solvents are used in the preparation process, and that low surface energy materials are difficult to disperse in water, the present invention synthesizes polyurethane by reacting dihydroxy mono-terminated polydimethylsiloxane with diisocyanate to form an urethane group, and adding a dihydroxy hydrophilic chain extender as a chain extender. First, the molecular chain segments in PDMS are flexible and can swing freely, so polydimethylsiloxane has a lower surface energy and excellent wetting properties; secondly, by utilizing the high reactivity of the hydroxyl groups in dihydroxy mono-terminated polydimethylsiloxane, its hydroxyl end can be fixed at the coating interface, and its long chain extends into the air phase, effectively forming a molecular brush structure. Finally, a hydrophilic group is introduced so that the polyurethane can be well dispersed in water to form an emulsion.
[0030] (2) The present invention can meet the water-repellent and anti-fouling requirements of fabrics. Taking cotton fabric and polyester fabric as examples, the water-repellent properties of the fabrics treated with the waterborne polyurethane coating having a polydimethylsiloxane molecular brush structure of the present invention are greatly improved, and the anti-graffiti, self-cleaning and antistatic properties are also greatly improved. Due to the presence of a large number of hydrophilic groups, the untreated cotton fabric itself has no hydrophobic ability and the contact angle is 0°. After treatment, the cotton fabric can be super-hydrophobic, and the contact angle can reach up to 157.1°. When graffiti is drawn on the untreated cotton fabric and the coated cotton fabric with a watercolor pen, the pigment will be dispersed on the untreated cotton fabric, and wiping with a wet wipe will not clean the pigment on the cloth; on the contrary, the pigment on the cotton fabric treated with the waterborne polyurethane coating will shrink, and wiping with a wet wipe can easily wipe off the pigment on the fabric. In addition, the waterborne polyurethane coating having a polydimethylsiloxane molecular brush structure prepared by the present invention has a dense cross-linked network, which further enhances the water resistance and wear resistance of the fabric after drying and curing.
[0031] (3) In addition, when the aqueous polyurethane coating liquid of the present invention is applied to transparent products such as glass and plastic, it is found that the aqueous polyurethane coating liquid of the present invention also has anti-fogging properties and can maintain good light transmittance of the transparent products. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein
[0033] Figure 1 The SEM images of the surfaces of untreated cotton fabric and cotton fabric treated with the aqueous polyurethane coating liquid prepared in Example 1, and the optical photographs of water droplets on the surface of the coated cotton fabric prepared in Example 1; wherein (a) the surface of untreated cotton fabric; (b) the surface of cotton fabric treated with the aqueous polyurethane coating prepared in Example 1; (c) the optical photograph of water droplets on the surface of cotton fabric treated with the aqueous polyurethane coating prepared in Example 1;
[0034] Figure 2 The SEM images of the cotton fabric treated with the aqueous polyurethane coating liquid prepared in Example 1 after four accelerated water washings are shown in the following figure; (a) the SEM image of the fabric surface after one accelerated water washing; (b) the SEM image of the fabric surface after two accelerated water washings; (c) the SEM image of the fabric surface after three accelerated water washings; (d) the SEM image of the fabric surface after four accelerated water washings;
[0035] Figure 3 The anti-graffiti performance test of cotton fabric treated with the aqueous polyurethane coating liquid prepared in Example 1;
[0036] Figure 4 is the sliding speed test of water droplets on untreated glass, coated glass of Example 5 and coated glass of Comparative Example 1;
[0037] Figure 5 It is the test diagram of electrostatic half-life and electrostatic voltage, (a) is the electrostatic half-life, (b) is the electrostatic voltage;
[0038] Figure 6 This is the anti-fog performance test of the aqueous polyurethane emulsion in Example 4. The test coating is coated on a glass slide, and the anti-fog performance of the coating and the anti-fog index are characterized by the light transmittance of the glass slide. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0040] In the following examples and comparative examples, cotton fabric is commercially available pure cotton plain fabric, and polyester fabric is commercially available pure polyester knitted fabric; dihydroxy mono-terminated polydimethylsiloxane was provided by Anhui Aiyota Silicone Oil Co., Ltd. and was analytically pure; isophorone diisocyanate was provided by San Chemical Technology (Shanghai) Co., Ltd. and was analytically pure; dibutyltin dilaurate was provided by Shanghai Aladdin Biochemical Technology Co., Ltd. and was analytically pure; polyethylene glycol was provided by Dalian Meilun Biotechnology Co., Ltd. and was chemically pure; 2,2-dihydroxymethylpropionic acid was provided by San Chemical Technology (Shanghai) Co., Ltd. and was chemically pure; dodecyl bis(hydroxyethyl)methylammonium chloride was provided by Xiamen Xianduan Technology Co., Ltd. and was chemically pure; triethylamine was provided by Jiangsu Qiangsheng Functional Chemical Co., Ltd. and was analytically pure; acetone was provided by Jiangsu Qiangsheng Functional Chemical Co., Ltd. and was analytically pure; silica nanoparticles, synthetic; monohydroxy di-terminated polydimethylsiloxane was provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd., 98%.
[0041] Example 1
[0042] (1) Add 4.89 g of dihydroxy mono-terminated polydimethylsiloxane and 1.7 g of polyethylene glycol into a three-necked flask under nitrogen atmosphere, add appropriate amount of acetone to dissolve, stir moderately and heat to the reaction temperature of 85°C;
[0043] (2) 2.11 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0044] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0045] (4) cooling the mixture prepared in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain an aqueous polyurethane coating liquid;
[0046] (5) The pure cotton fabric was immersed in the water-based polyurethane coating liquid for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain a water-based polyurethane coating fabric with a molecular brush-like structure.
[0047] Example 2
[0048] The preparation method of Example 2 is the same as that of Example 1, except that hydrophobic nano-silicon dioxide particles are added to Example 2. The specific steps are as follows:
[0049] (1) Add 4.89 g of dihydroxy mono-terminated polydimethylsiloxane and 1.7 g of polyethylene glycol into a three-necked flask under nitrogen atmosphere, add appropriate amount of acetone to dissolve, stir moderately and heat to the reaction temperature of 85°C;
[0050] (2) 2.11 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0051] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0052] (4) cooling the mixture obtained in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain a waterborne polyurethane coating;
[0053] (5) adding hydrophobic nano-silica particles with a solid content of 5% to the aqueous polyurethane coating, stirring evenly for 2 hours, and obtaining an aqueous polyurethane coating liquid containing hydrophobic nano-silica particles with a concentration of 5%;
[0054] (6) The pure cotton fabric is immersed in the aqueous polyurethane coating liquid prepared in step (5) for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain an aqueous polyurethane coating fabric having a molecular brush-like structure.
[0055] Example 3
[0056] The preparation method of Example 3 is the same as that of Example 2, except that the fabric impregnated in Example 2 is polyester fabric. The specific steps are as follows:
[0057] (1) Add 4.89 g of dihydroxy mono-terminated polydimethylsiloxane and 1.7 g of polyethylene glycol into a three-necked flask under nitrogen atmosphere, add appropriate amount of acetone to dissolve, stir moderately and heat to the reaction temperature of 85°C;
[0058] (2) 2.11 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0059] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0060] (4) cooling the mixture prepared in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain an aqueous polyurethane solution;
[0061] (5) Adding hydrophobic nano-silica particles equivalent to 5% of the solute mass into the aqueous polyurethane solution and stirring evenly for 2 hours to obtain an aqueous polyurethane fabric coating liquid with a molecular brush-like structure.
[0062] (6) The polyester fabric is immersed in the aqueous polyurethane coating liquid prepared in step (5) for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain an aqueous polyurethane coating fabric having a molecular brush-like structure.
[0063] Example 4
[0064] The preparation method of Example 4 is the same as that of Example 1, except that 1.01 g of 2,2-dihydroxymethylpropionic acid in Example 1 is replaced with 0.2 g of dodecyl bis(hydroxyethyl)methylammonium chloride. The specific steps are as follows:
[0065] (1) Add 25.5 g of dihydroxy mono-terminated polydimethylsiloxane and 2 g of polyethylene glycol into a three-necked flask under nitrogen atmosphere, add appropriate amount of acetone to dissolve, stir moderately and heat to the reaction temperature of 85°C;
[0066] (2) 1.67 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0067] (3) 0.2 g of dodecyl bis(hydroxyethyl)methyl ammonium chloride was added into a three-necked flask and the reaction temperature was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the polymer viscosity to avoid gelation.
[0068] (4) dispersing with distilled water at a high speed of 1500 rpm to obtain an aqueous polyurethane coating liquid;
[0069] (5) The polyester fabric was immersed in the water-based polyurethane coating liquid for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain a water-based polyurethane coating fabric with a molecular brush-like structure.
[0070] Example 5
[0071] Example 5 is prepared in the same manner as Example 1, except that 4.89 g of dihydroxy mono-blocked polydimethylsiloxane in Example 1 is replaced with 3.89 g of dihydroxy mono-blocked polydimethylsiloxane, and 2.11 g of isophorone diisocyanate is replaced with 2.03 g of isophorone diisocyanate. The specific steps are as follows:
[0072] (1) 3.89 g of dihydroxy mono-terminated polydimethylsiloxane and 1.7 g of polyethylene glycol were added to a three-necked flask in a nitrogen atmosphere, and an appropriate amount of acetone was added to dissolve the mixture. The mixture was stirred and heated to a reaction temperature of 85°C.
[0073] (2) 2.03 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0074] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0075] (4) cooling the mixture prepared in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain an aqueous polyurethane coating liquid;
[0076] (5) The pure cotton fabric was immersed in the water-based polyurethane coating liquid for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain a water-based polyurethane coating fabric with a molecular brush-like structure.
[0077] Example 6
[0078] The preparation method of Example 6 is the same as that of Example 1, except that 4.89 g of dihydroxy mono-terminated polydimethylsiloxane in Example 1 is replaced by 5.89 g of dihydroxy mono-terminated polydimethylsiloxane, and 2.11 g of isophorone diisocyanate is replaced by 2.30 g of isophorone diisocyanate. The specific steps are as follows:
[0079] (1) Add 5.89 g of dihydroxy mono-terminated polydimethylsiloxane and 1.7 g of polyethylene glycol into a three-necked flask under nitrogen atmosphere, add appropriate amount of acetone to dissolve, stir moderately and heat to the reaction temperature of 85°C;
[0080] (2) 2.20 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0081] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0082] (4) cooling the mixture prepared in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain an aqueous polyurethane coating liquid;
[0083] (5) The pure cotton fabric was immersed in the water-based polyurethane coating liquid for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain a water-based polyurethane coating fabric with a molecular brush-like structure.
[0084] Example 7
[0085] The preparation method of Example 7 is the same as that of Example 2, except that the isophorone diisocyanate in Example 2 is replaced by hexamethylene diisocyanate. The specific steps are as follows:
[0086] (1) Add 4.89 g of dihydroxy mono-terminated polydimethylsiloxane and 1.7 g of polyethylene glycol into a three-necked flask under nitrogen atmosphere, add appropriate amount of acetone to dissolve, stir moderately and heat to the reaction temperature of 85°C;
[0087] (2) 2.15 g of hexamethylene diisocyanate was added dropwise to a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0088] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0089] (4) cooling the mixture prepared in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain an aqueous polyurethane solution;
[0090] (5) Adding hydrophobic nano-silica particles equivalent to 5% of the solute mass into the aqueous polyurethane solution and stirring evenly for 2 hours to obtain an aqueous polyurethane fabric coating liquid with a molecular brush-like structure.
[0091] (6) The polyester fabric is immersed in the aqueous polyurethane coating liquid prepared in step (5) for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain an aqueous polyurethane coating fabric having a molecular brush-like structure.
[0092] Comparative Example 1
[0093] Comparative Example 1 has the same steps as Example 1, except that no dihydroxy mono-terminated polydimethylsiloxane is added to Comparative Example 1, and only 4 g of polyethylene glycol is added. The specific steps are as follows:
[0094] (1) Add 4 g of polyethylene glycol into a three-necked flask under nitrogen atmosphere, add appropriate amount of acetone to dissolve, stir moderately and heat to the reaction temperature of 85°C;
[0095] (2) 2.11 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0096] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0097] (4) cooling the mixture prepared in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain an aqueous solution;
[0098] (5) The pure cotton fabric was immersed in the aqueous solution for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain the fabric.
[0099] Comparative Example 2
[0100] The steps of Comparative Example 2 are the same as those of Example 1, except that 4.89 g of dihydroxy mono-terminated polydimethylsiloxane is replaced with 4.83 g of monohydroxy di-terminated polydimethylsiloxane in Comparative Example 2. The specific steps are as follows:
[0101] (1) Add 4.83 g of monohydroxy di-terminated polydimethylsiloxane and 1.7 g of polyethylene glycol into a three-necked flask under nitrogen atmosphere, add appropriate amount of acetone to dissolve, stir moderately and heat to the reaction temperature of 85°C;
[0102] (2) 2.11 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0103] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0104] (4) cooling the mixture prepared in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain an aqueous polyurethane coating liquid;
[0105] (5) The pure cotton fabric was immersed in the water-based polyurethane coating liquid for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain a water-based polyurethane coated fabric.
[0106] Comparative Example 3
[0107] Comparative Example 3 is the same as Example 1, except that 1.7 g of polyethylene glycol is replaced with 0.155 g of trihydroxypropane in Comparative Example 1. The specific steps are as follows:
[0108] (1) 4.89 g of dihydroxy mono-terminated polydimethylsiloxane and 0.155 g of trihydroxypropane were added to a three-necked flask in a nitrogen atmosphere, and an appropriate amount of acetone was added to dissolve the mixture. The mixture was stirred and heated to a reaction temperature of 85°C.
[0109] (2) 2.11 g of isophorone diisocyanate was added dropwise into a three-necked flask, and dibutyltin dilaurate was added as a catalyst, and the temperature was maintained at 85° C. for 30 min;
[0110] (3) 1.01 g of 2,2-dimethylolpropionic acid was added to a three-necked flask and the reaction was maintained at 85° C. for 2 h. During the reaction, acetone was added to adjust the viscosity of the polymer to avoid gelation.
[0111] (4) cooling the mixture prepared in step (3) to room temperature, adding triethylamine as a neutralizing agent, neutralizing and stirring for 10 minutes, and then dispersing with distilled water at a high speed of 1500 rpm to obtain a waterborne polyurethane coating;
[0112] (5) The pure cotton fabric and the polyester fabric were immersed in the waterborne polyurethane coating for 5 minutes, and dried and cured at 120° C. for 30 minutes to obtain a waterborne polyurethane coated fabric with a molecular brush-like structure.
[0113] Performance Testing
[0114] 1. Water contact angle test: The prepared coated fabric was cut into strips of 1 cm×5 cm and flatly attached to a glass sheet. The test was performed using a video contact angle meter from KRUSS GmbH of Germany. The contact angle data are shown in Table 1.
[0115] Table 1 Contact angle data of Examples 1-7 and Comparative Examples 1-3
[0116] Water contact angle (°) Error margin Example 1 155.3 ±1.2 Example 2 157.1 ±1.0 Example 3 154.3 ±0.3 Example 4 155.1 ±1.3 Example 5 152.0 ±1.6 Example 6 152.7 ±1.3 Example 7 153.2 ±1.2 Comparative Example 1 0 / Comparative Example 2 151.3 ±1.4 Comparative Example 3 156.0 ±1.9
[0117] Compared with Comparative Example 1, the contact angle of Example 1 is close to that of Comparative Example 1, indicating that the waterborne polyurethane coating prepared by the present invention has no lower waterproof performance than the non-aqueous polyurethane coating. Examples 1-7 show extremely high water contact angles, indicating that the waterborne polyurethane coating prepared by the present invention can significantly improve the waterproof and antifouling properties of the fabric. Compared with Comparative Example 2, Example 1 uses a dihydroxyl single-terminated polydimethylsiloxane, while Comparative Example 2 uses a monohydroxyl double-terminated polydimethylsiloxane. The double-terminated has a hydroxyl group on both sides, and both react in the reaction system, so the entire macromolecular long chain is fixed at the coating interface. The single-terminated has only one section with a hydroxyl group, and the hydroxyl end is reacted and fixed at the coating interface. The other end, due to its low surface energy, will extend to the air phase to form a liquid-like surface, and the droplets are easy to slide on it. Both are polydimethylsiloxanes, so there is not much difference in contact angle, but in terms of easy sliding and easy decontamination, the single-terminated is more excellent.
[0118] 2. Antifouling performance test: Figure 3 As shown in the figure, when drawing with watercolor pens on untreated cotton fabric and coated cotton fabric, the pigment will disperse on the untreated cotton fabric, and wiping with wet wipes will not clean the pigment on the fabric; on the contrary, the pigment on the coated cotton fabric will shrink, and wiping with wet wipes can easily wipe off the pigment on the fabric. In addition, the coated cotton fabric shows excellent wetting properties for various liquids. When drawing with watercolor pens, the pigment is quickly absorbed by the untreated cotton fabric, and wiping with wet wipes cannot clean the pigment on the fabric (see Figure 3 a); and when the cotton fabric in Example 1 is painted, the pigment is not absorbed and can be completely removed by gently wiping with wet wipes (see Figure 3 b); When drawing on cotton fabric in Comparative Example 1, the pigment was partially absorbed and the wet wipes could only remove part of the pigment (see Figure 3 c) This result proves that the polyurethane coating with a "molecular brush-like" structure has better anti-crow function
[0119] 3. Washing resistance test: Example 1 and Comparative Example 3 were subjected to accelerated washing according to AATCC 61, and each accelerated washing was equivalent to five machine washings. After each washing, the sample was subjected to a water contact angle test, and the contact angle data are shown in Table 2. The contact angle of the waterborne polyurethane coated fabric of Comparative Example 3 dropped to below 120° after one accelerated washing, indicating that the washing resistance of the coating was significantly reduced after polyethylene glycol was replaced with trihydroxymethane.
[0120] Table 2 Water wash resistance test of samples of Example 1
[0121] Water contact angle (°) Error margin No accelerated water washing 155.3 ±1.3 Accelerated water wash 1 time 153.2 ±0.9 Accelerated water washing 2 times 152.6 ±0.2 Accelerated washing 3 times 152.0 ±0.9 Accelerated washing 4 times 151.9 ±0.7 Accelerated washing 5 times 151.5 ±1.6
[0122] 4. Antistatic property test: The antistatic property is evaluated according to GB / T 12703.1-2008 standard. The electrostatic half-life and electrostatic voltage of the fabric are measured at a temperature of 20°C and a relative humidity of 40% using a H0110 V2 electrostatic charge decay tester. According to the standard, Example 1 is rated as Class A, Example 4 is rated as Class A, and Comparative Example 3 is rated as Class C.
[0123] 5. Anti-fog performance test: The anti-fog performance was tested by the hot and cold method. The half-coated glass slide was placed in a refrigerator (-5°C) for 30 minutes, then exposed to the laboratory environment (20°C, 40% relative humidity), and the glass slide was immediately photographed. In addition, the transmittance values of the uncoated and coated parts of the glass slide at 400-800nm were tested using a Jena S600 spectrophotometer. The results show that Example 4 has excellent anti-fog performance.
[0124] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing an aqueous polyurethane coating liquid, characterized in that: The following steps are involved: S1, heating the dihydroxy mono-terminated polydimethylsiloxane, the terminal hydroxyl oligomer and the diisocyanate in the presence of an organic solvent and a catalyst to obtain a polyurethane prepolymer; S2, heating the polyurethane prepolymer and the dihydroxy hydrophilic chain extender to react to obtain polyurethane; S3, mixing the polyurethane with a neutralizing agent, and dispersing them in water at a high speed to obtain the aqueous polyurethane coating liquid.
2. The preparation method according to claim 1, characterized in that: In step S3, the aqueous polyurethane coating liquid further comprises hydrophobic nano-silicon dioxide, wherein the mass ratio of the hydrophobic nano-silicon dioxide to the aqueous polyurethane coating liquid is (2-10):
100.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the dihydroxy mono-terminated polydimethylsiloxane to the terminal hydroxyl oligomer in step S1 is (2-8):
1.
4. The preparation method according to claim 1, characterized in that: The dihydroxy hydrophilic chain extender in step S1 is selected from one or more of 2,2-dihydroxymethyl propionic acid, dodecyl dihydroxyethyl methyl ammonium chloride, and bis(2-hydroxyethyl) dimethyl ammonium chloride.
5. The preparation method according to claim 1, characterized in that: The hydroxyl-terminated oligomer in step S1 is selected from one or more of hydroxyl-terminated polyethylene glycol, polypropylene glycol, polybutylene glycol, and polybutadiene, wherein the molecular weight of the hydroxyl-terminated oligomer is 1000-3000; The diisocyanate in step S1 is selected from one or more of isophorone diisocyanate and hexamethylene diisocyanate; The organic solvent in step S1 is selected from one or more of acetone, ethyl acetate, butanone, tetrahydrofuran, N,N-dimethylformamide, and dichloromethane; The catalyst in step S1 is selected from one or more of dibutyltin dilaurate, dimethylcyclohexylamine, and N,N-dimethylbenzylamine; The neutralizing agent in step S3 is selected from one or more of triethylamine, dimethylethanolamine, diethylethanolamine, triethanolamine, N,N-dimethylethanolamine, and diethanolamine.
6. The preparation method according to claim 1, characterized in that: The temperature of the heating reaction in step S1 is 70-90°C, and the time of the heating reaction is 15min-3h; The temperature of the heating reaction in step S2 is 70-90° C., and the time of the heating reaction is 15 min-3 h.
7. The preparation method according to claim 1, characterized in that: Steps S1-S3 are performed under an inert gas atmosphere.
8. An aqueous polyurethane coating liquid prepared by the preparation method according to any one of claims 1 to 7.
9. A waterproof, anti-graffiti and anti-static coating, characterized in that: The waterproof, anti-graffiti and antistatic coating is prepared from the aqueous polyurethane coating liquid according to claim 8.
10. A waterproof, anti-graffiti and anti-static product, characterized in that: The waterproof, anti-graffiti and anti-static product contains the waterproof, anti-graffiti and anti-static coating according to claim 9.
Citation Information
Patent Citations
Preparation method of non-fluorine traceless anti-fouling water-based polyurethane self-stratifying coating
CN115074014A
Preparation method and application of hydrophobic modified polyurethane nano composite material
CN118725241A
Hydrophilic water-dispersive polyurethane resin for textile coating and manufacturing process thereof
KR1020170111865A
Cited By
Double-bond-terminated cationic organosilicon waterborne polyurethane, preparation method thereof, anti-fog sterilization hydrogel and anti-fog sterilization coating
CN122356433A